Income Tax Rates and Earnings Management in Indonesian Consumer Goods: Tarif Pajak Penghasilan Korporasi dan Manajemen Laba pada Industri Barang Konsumsi: Analisis Empiris di Indonesia - Mai Widyastuti; Herman Ernadi (Academia Open, 2023)
This study investigates the influence of changes in corporate income tax rates, tax planning, and company size on earnings management in the consumer goods industry in Indonesia. A purposive sampling method is adopted, including a sample of 16 consumer goods industrial companies listed on the Indonesia Stock Exchange from 2015 to 2019. Secondary data analysis is conducted using SPSS 23. The findings reveal that changes in corporate income tax rates have a negative and significant impact on earnings management. However, tax planning does not show a significant effect on earnings management, and firm size does not exert a significant influence on earnings management. These results contribute to the understanding of factors influencing earnings management practices in the consumer goods industry and have implications for regulatory authorities and stakeholders in enhancing transparency and financial reporting quality. The findings highlight the importance of considering corporate income tax rates as a significant determinant of earnings management practices in the consumer goods industry in Indonesia, thereby providing valuable insights for policymakers, researchers, and professionals in the field of accounting and finance. Highlights: Changes in corporate income tax rates have a significant negative impact on earnings management in the consumer goods industry. Tax planning does not significantly affect earnings management in the consumer goods industry. Firm size does not exert a significant influence on earnings management in the consumer goods industry. Keywords: corporate income tax rates, earnings management, consumer goods industry, Indonesia, financial reporting quality.